Navigating Workplace Diversity: The Roles Of Core Self-Evaluation And Emotional Intelligence In Conflict Management - Rosita, Sry; Musnaini; Aira, Dian Mala Fithriani; Tialonawarmi, Feny (Jurnal Manajemen Indonesia, 2025)
The study aims to assess the direct impacts of core self-evaluation and emotional intelligence on workplace conflict and determine Diversity's mediating role in this relationship. Additionally, it seeks to understand the broader implications of these interactions for conflict management and diversity initiatives within the workplace. The research utilized a quantitative approach to distribute questionnaires to 94 lecturers to capture data on the specified variables. These results support developing targeted training programs that enhance emotional intelligence and effectively manage Diversity to mitigate workplace conflicts. Furthermore, the study advocates for organizational policies that foster inclusion, encourage open dialogue, and respect for Diversity, thereby promoting a healthy and inclusive work environment. This study contributes valuable insights into the factors influencing workplace conflict in academic settings. It highlights the crucial roles of self-evaluation, emotional intelligence, and Diversity in managing conflict and fostering a productive, inclusive workplace.